Síntese e caracterização de cerâmicas ferroelétricas de BaTiO3 modificadas com Sm3+ - Oliveira, Marco Aurélio de (2012)
In this work, the physical properties of the rare earth modified BaTiO3 system, specifically with the Sm3+ ion, have been investigated. The structural, micro-structural, ferroelectric, dielectric and electric properties were analyzed as a function of the samarium content by considering the Ba1-xSmxTiO3 chemical formula (x = 0, 0.001, 0.002, 0.003 e 0.005). The materials were obtained from the Pechini´s method (or polymeric precursors method), well known in the current literature for its efficiency, when compared to conventional methods commonly used for obtaining ceramic materials. In this way, the Pechini´s method shows several advantages such as low synthesis temperatures, low levels of contaminations, high stoichiometric control and homogenization, and the possibility for obtaining nano-metric scaled powders. All of these characteristics allow to obtain high density ceramics. The study of the structural and micro-structural properties were performed in order to confirm the desired ferroelectric phases, from the x-ray diffraction and scanning electronic microscopy techniques, respectively. For all the cases, the dielectric and electric properties were investigated in a wide frequency and temperature range. The obtained results have been discussed according the current theories reported in the literature. In particular, it was analyzed the conductive effects provided from the rare earth doping, viewing to better understand the factors, which influence and determine the semiconductor characteristics of such materials. These factors allow to focuses the response of the studied materials for furthers applications in the electro-electronic industry.